Biodegradation of PAHs by Burkholderia sp. VITRSB1 Isolated from Marine Sediments. (28th October 2015) - Revathy, T.; Jayasri, M. A.; Suthindhiran, K.
Abstract : The polycyclic aromatic hydrocarbons (PAHs) pollution to the environment is a major threat to the living organisms, and hence the degradation of these PAHs is necessary. Studies on PAHs degrading bacteria have focussed on terrestrial microbes and the potential of marine derived microbes is undermined. Herein we report the isolation and characterization of PAHs degrading Burkholderia sp. from lagoon sediments collected at the Southern coast of India. The strain was Gram negative, rod-shaped, motile, and ∼2–5 μ m in length. Based on the phylogenetic data the strain was identified as Burkholderia and designated as VITRSB1. Initial PAHs degradation ability of the strain was assessed using basal salt medium supplemented with diesel, kerosene, toluene, aniline, naphthalene, and phenol. The strain was found to be effectively degrading kerosene, diesel, toluene, and aniline even at higher concentration (1%). However, naphthalene and aniline were degraded only at lower concentration (0.1%) and phenol, camphor, and DAP inhibited the growth of the strain. Furthermore, the degraded end products of the PAHs were determined using FTIR. Notably, none of the end products were found to be toxic to the biosphere. Our results indicate that the isolated Burkholderia sp. could be a prospective candidate for the effective degradation of selective PAHs.